2017
DOI: 10.12816/0038702
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries and Gingivitis Associated with Mutans Streptococci among Children

Abstract: Background Dental Caries is the most prevalent oral disease among children caused by Streptococci mutans, which produces acids that cause tooth surface breakdown and subsequent formation of cavity which encourage growth of bacterial biofilms and cause the gingivitis.Objective The aim was to assess the prevalence of dental Caries and severity of gingivitis among school children and to correlate it with the Streptococcus mutans counts. Materials and Methods Five hundred and eighty (580) school children participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…The present study results are in contrast with Iraqi studies that found no significant relationship between the mean number of decayed, missing, and filled primary teeth (dmft) and the number of (S. mutans), attempting to demonstrate and encourage the principle that tooth decay is a multifactorial disease influenced by a number of factors (25,26) .…”
Section: Discussioncontrasting
confidence: 99%
“…The present study results are in contrast with Iraqi studies that found no significant relationship between the mean number of decayed, missing, and filled primary teeth (dmft) and the number of (S. mutans), attempting to demonstrate and encourage the principle that tooth decay is a multifactorial disease influenced by a number of factors (25,26) .…”
Section: Discussioncontrasting
confidence: 99%